HIDROGEOQUIMICA DE ACUIFEROS COSTEROS, SAN CLEMENTE DEL TUYU. PROVINCIA DE BUENOS AIRES, REPUBLICA ARGENTINA - barabagallo, josé; VIZCAINO, ALEIJANDRO; ARZAC, RICARDO GONZÁLEZ; ALFONSO, FRANCISCO CAMPOS (Águas Subterrâneas, 1994)
RESUMO NAO DISPONIVEL